A Study On The Frequency Of Different Types Of Optical Low Vision Aids Prescribed For Low Vision Patients Examined In The Clinic Of Optometry, Faculty Of Rehabilitation Sciences Shahid Beheshti University Of Medical Sciences, Tehran, 1387 - Mohammad Ghassemi Broumand; Mohsen akhgary; Seyed Mehdi Tabatabaee; Mohammad Aghazadeh Amiri; Azam Karimi (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: Different diseases can be the cause of low vision. In the case of low vision, visual acuity with conventional optical devices such as glasses and contact lenses is between" 20/70 to 20/200". To improve the visual performance in these patients, low vision aids are prescribed.The types of prescribed low vision aids vary in different diseases. The purpose of this study is to determine the type and frequency of optical aids prescribed for low vision patients examined in optometry clinic of Rehabilitation faculty of shahid Beheshti University in 1387. Materials and Methods: In this retrospective cross-sectional study, 204 low vision patients went under investigation. In the present study variables including type and rate of refractive error, visual acuity with the best correction, type of diseases and type of prescribed optical low vision aids were investigated.Results: The frequency of prescribed distance glasses in diabetic retinopathy was 97%, age related macular degeneration 86.2%, Stargarts 92%, retinitis pigmentosa 86.4% and albinism 88.2%, Also the frequency of prescribed microscope in diabetic retinopathy was 81.82% , age related macular degeneration 48.27%, Stargarts 40% , retinitis pigmentosa 35.3% , albinism 35.3% and the frequency of prescribed magnifier in diabetic retinopathy was18.18%, age related macular degeneration 24.12% , Stargarts 52%, retinitis pigmentosa18.18% and albinism 29.4%.Conclusion: In many low vision conditions, it is more suitable to prescribe distance glasses rather than telescope. In this study the distance glass with the frequency of 84.8% is seen more acceptable in comparison with the telescope with the frequency of 41.7%. Among near optical low vision aids, microscope with the frequency of 50.5% is more accepted by the patients compared to magnifier with the frequency of 26% and CCTV with the frequency of 0.50%.